Case Studies on Managing Government Compensation and Employment : Institutions, Policies, and Reform Challenges. (Policy Papers; Policy Paper ;, 2016)
This supplement presents country case studies reviewing country experiences with managing wage bill pressures, which are the basis for the compensation and employment reform lessons identified in the main paper. The selection of countries for the case studies reflects past studies carried out by either the IMF or the World Bank in the context of technical assistance or bilateral surveillance (Table 1). These studies provide important insights into the different sources of wage bill pressures as well as the reform challenges governments have faced when addressing these pressures over the short and medium term. The studies cover 20 countries, including five advanced economies, six countries from sub-Saharan Africa, two countries in developing Asia, one country in the Middle East and North Africa, three countries in Latin America and the Caribbean, and three countries in Central and Eastern Europe and the CIS. The structure of each case study is similar, with each study starting with a presentation of the institutional coverage and framework for setting and managing the wage bill; a description of employment and compensation levels, including their comparison with the private sector; and a discussion of the challenges that motivated the need for reforms and, when applicable, the reforms implemented and lessons derived from these.